2019
DOI: 10.1007/s11083-019-09502-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Dushnik-Miller Dimension, Boolean Dimension and Local Dimension

Abstract: The original notion of dimension for posets is due to Dushnik and Miller and has been studied extensively in the literature. Quite recently, there has been considerable interest in two variations of dimension known as Boolean dimension and local dimension. For a poset P , the Boolean dimension of P and the local dimension of P are both bounded from above by the dimension of P and can be considerably less. Our primary goal will be to study analogies and contrasts among these three parameters. As one example, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The following lemma is analogous to a lemma proved for local dimension by Barrera-Cruz, Prag, Smith, Taylor, and Trotter in [1].…”
Section: Local 2-dimension and Complete Bipartite Edge-coverings Of G...mentioning
confidence: 62%
“…The following lemma is analogous to a lemma proved for local dimension by Barrera-Cruz, Prag, Smith, Taylor, and Trotter in [1].…”
Section: Local 2-dimension and Complete Bipartite Edge-coverings Of G...mentioning
confidence: 62%
“…In [1], it is shown that for each d 1, there is a poset P with bdim(P ) 4 and ldim(P ) > d. Our construction provides another instance of a family of posets where Boolean dimension is bounded and local dimension is not.…”
Section: Bounded Boolean Dimension and Unbounded Local Dimensionmentioning
confidence: 96%
“…Barrera-Cruz, Prag, Smith, Taylor and Trotter [1] proved that the local dimension of a poset is bounded in terms of the path-width of its cover graph, independent of its height. Formally, here is their result.…”
Section: Structural Graph Theorymentioning
confidence: 99%
See 2 more Smart Citations